Anisotropy of the Conductivity in the Asymmetric Quantum Wells - Majchrowski, Klaudiusz; Paśko, Wioletta (ACTA PHYSICA POLONICA A, 2008)
Gorbatsevich et al. and Kibis suggested that a number of interesting galvano-magnetic effects could be observed in quantum structures where the symmetry with respect to the space coordinates inversion and time- -reversal are broken simultaneously. In the paper of Kibis for example, the in¯nite triangular quantum well in an external magnetic field was considered and the anisotropy of electron momentum transfer due to interaction with phonons was predicted. The role of magnetic ¯eld was to provide the time- -invariance breaking. In this work we considered the e®ect of anisotropy of electron momentum transfer due to interaction with polarized light using more realistic model of ¯nite triangular quantum well. This anisotropy leads to the anisotropy of the real part of photoconductivity and as it follows from our calculations, the e®ect though not very great, could be measurable for the attainable values of magnetic ¯eld B ¼ 5 T and the widths of quantum well.